ДІАГНОСТИКА РЕГІОНАЛЬНИХ ВІДМІННОСТЕЙ СИСТЕМИ УПРАВЛІННЯ КАДРОВИМ ПОТЕНЦІАЛОМ В СУЧАСНИХ УМОВАХ - Vuychenko, Maryna (Zhytomyr Ivan Franko State University, 2024)
The article notes that in the conditions of war in which our country is currently located, an important issue is the development of measures to regulate objective processes in the labor market caused by the departure of a significant number of qualified specialists abroad, the movement of the employed population from region to region, and the mobilization of a significant part of the economically active population. The article indicates that within the framework of this problem, the main task is to improve the interaction between the central government and local government bodies, taking into account the real state of the military, economic, demographic, social, political, and humanitarian situation. It is necessary to significantly expand the powers of territorial communities in all spheres of public life. Management by peaceful methods during war is impossible. This is especially relevant, since the administrative and territorial reform has not yet been completed and is closely related to the results of hostilities. The article notes that the war has imposed new requirements on the style of personnel management. The main thing is to preserve labor capital and increase the efficiency of employees. The management system should be flexible and economically justified and legally impeccable. This approach assumes a certain freedom of decisions and actions of managers. A state of emergency allows for extraordinary organizational measures, in particular in the field of logistics of goods and services. The article notes that the regulatory documents that we have already analyzed emphasize that during martial law, the freedom of decisions and actions for managers of organizations may be limited. The instability of the political and economic situation can lead to a disruption of investment in production and the supply of products and spare parts, as well as electricity, which in turn can increase the risk of injuries, violations of labor discipline, and staff turnover. Preservation of labor potential is a priority for every manager. For this, it is necessary to use various forms and means of stimulating personnel. Management practice has developed such forms of employee encouragement as mutual support and cooperation, material and moral incentives, training and development, advanced training, and prospects for professional and career growth.